A National Survey on Supporting K–12 Teachers in Cambodia through Professional Development and Teaching Guides - Hornmann Banh (Journal of General Education and Humanities, 2025)
A three-week cross-sectional online survey of 2,199 Cambodian K–12 teachers used descriptive statistics and cross-tabulations, complemented by chi-square tests, to pinpoint (a) pressing classroom challenges, (b) preferred professional-development formats, and (c) needs for instructional guides. Results showed that 59.8% of teachers wanted support for slow learners, 55.8% for classroom management, and 39.2% for low-tech digital integration; an overwhelming 93.3% favoured short workshops (1–2 days) or medium-length hybrid courses (1–3 months) with follow-up coaching via Telegram; and 60.6 % requested step-by-step lesson guides aligned with national textbooks, ideally as portable booklets and mobile-friendly PDFs. Chi-square tests confirmed that the pattern of classroom challenges varied significantly by grade level (χ²(36, n = 2,199) = 108.34, p < 0.001), whereas demand for ready-made guides was statistically uniform across school types (χ²(16, n = 2,199) = 18.01, p = 0.323). The findings support a compact yet sustained professional development model that begins with practice-focused workshops, embeds ongoing online mentoring, and equips teachers with bilingual visual guides—offering a realistic pathway for translating Cambodia’s ambitious education reforms into daily classroom gains.